Theatrical Education Versus Social Development of Students with Intellectual Disabilities (Based on the Activities Carried Out by the Complex of Special Schools in Czerwionka-Leszczyny, Polska) - Olimpia Gogolin; Eugeniusz Szymik (Vasyl Stefanyk Precarpathian National University, 2024)
The purpose of the article is to substantiate the importance of theatre education in the social development of younger pupils of special schools. The theoretical part presents the theatre education of students with special educational needs, outlines the portrait of students with intellectual disabilities and defines the specifics of the activities of the Complex of Special Schools in Czerwionka-Leszczyny. The practical part of the article presents theatre education in the Complex of these schools based on interviews with the leaders of the drama club and group "Zetki", on the school's journal and the results of the survey conducted amongst the members of the group. The article proves that theatrical activity promotes integration through the development of interpersonal skills and verbal and non-verbal communication, improvement of visual-hearing-motor coordination, as well as the formation of a sense of empathy and imagination of persons with disabilities. The importance of a friendly atmosphere and mutual acceptance of all participants during theatre activities is emphasised. The authors use the method of theoretical analysis of scientific sources on the research topic; the method of survey, as well as the analysis of the results of empirical research.